The E-Book of Arabic Online Based on Rushdi Ahmed Tuaima’s Theory - Ahmad Nuruddin Thaifur (Journal of Arabic Language Studies and Teaching, 2022)
Learning Arabic will only develop if we analyse the textbooks used. This study aims to analyse the electronic book of Arabic Online based on Tua'ima's theory. The assessment of this book is based on Tuaima's theory that this book is ideal, based on the preparation of book material following Tuaima's theory in preparing teaching materials. The theory consists of the general statements of the book, its output, the basis of its composition, language, linguistic skills, cultural teaching, and training. As for the research methodology in this study, the researcher used a descriptive literature study, and the types of research data were words and sentences consisting of a book. The data sources are books or references and lecturers who are experts in teaching Arabic. Among the research tools are observation and interviews, and the data collection methods used for research are reading and classification.